Pembentukan Paguyuban Sebagai Wadah Interaksi Antarpelaku UMKM di Desa Kedungpari - Fikriyatun Nabila; Syamsul Huda; Anisa Fitria Utami (Jurnal Pengabdian Masyarakat Nusantara, 2023)
. The potential of Kedungpari Village, Mojowarno District, Jombang Regency has potential for MSMEs compared to the potential for cultural heritage or natural tourism potential. KKNT MBKM East Java Veterans National Development University group of 20 successfully held the Kedungpari Duwe Gawe culinary tourism festival. Through this activity MSME actors try to open up by conveying the constraints or problems faced by MSME actors including MSME licensing, halal certification, MSME development which is still lacking in knowledge, as well as problems with marketing and so on. Thus the solution given is to form an MSME community as a forum for MSME actors in more focused development and solving problems that each MSME has through BUMDes which is the manager and person in charge of the association. The goal is for the community to become a forum for interaction and aspirations. The method used is based on the results of a field survey and data collection on MSMEs in the village of Kedung Pari.